Reduction and Association of the Lunotriquetral Ligament for Reverse Perilunate Dislocation - Huang, Hui-Kuang; Tsai, Tung-Yeh; Wang, Jung-Pan (Journal of Wrist Surgery, 2019)
Background Reverse perilunate injuries are rare. Contrary to perilunate injuries, the violent force would start from the lunotriquetral ligament, go reversely toward the radial side, and cause the reverse or ulnar-sided perilunate dislocation.Case Description We describe a 31-year-old man with a reverse perilunate dislocation, who presented to our institution 3 weeks after a motorcycle accident. The patient was successfully treated with the reduction and association of the lunate and triquetrum (RALT) procedure by using closed maneuver and percutaneous headless compression screw fixation. The patient can obtain a good radiographic result and satisfactory function at the 30-month follow-up.Literature Review Many case series were reported concerning the perilunate injuries. However, few cases of reverse perilunate dislocation have been reported in the literature. No cases of reverse perilunate dislocation treated 3 weeks after the injury with the RALT procedure have been reported.Clinical Relevance In this case, we found that the dislocation could still be reduced with the closed maneuver. With the RALT procedure, the carpal alignment can be maintained and the stability can be regained. Also, the functional outcomes are good.
Keywords: carpal dislocation; lunotriquetral ligament; RALT; perilunate; reverse